Rating of perceived exertion and blood lactate concentration during submaximal running - Steed, J.; Gaesser, G. A.; Weltman, A. (Medicine & Science in Sports & Exercise, 1994)
RPE was found to be a physiologically valid tool for prescribing exercise intensity when the intent is to use lactate threshold or blood lactate concentrations as the intensity criterion.